Variation and grammaticalization in Romance: a cross-linguistic study of the subjunctive - Poplack, Shana; Cacoullos, Rena Torres; Dion, Nathalie; Berlinck, Rosane de Andrade [UNESP]; Digesto, Salvatore; Lacasse, Dora; Steuck, Jonathan; AyresBennett, W.; Carruthers, J. (Walter De Gruyter Gmbh, 2018)
Building on studies seeking to position the Romance languages on the cline of grammaticalization, this study targets the evolution of subjunctive into subordination marker in speech corpora of French, Italian, Portuguese and Spanish. By considering the conditioning of variation between subjunctive and indicative in complement clauses, we operationalize parameters of late-stage grammaticalization, and establish measures of productivity. Results show that, with the exception of Spanish, subjunctive selection is constrained neither by contextual elements consistent with its oft-ascribed meanings nor by semantic classes of governors harmonic with such meanings. Instead, in all four languages, lexical bias is the major predictor of subjunctive selection, abetted by structural elements of the linguistic context. The overriding processes are lexical routinization, which is language-particular, with cognate governors displaying idiosyncratic associations with the subjunctive, and structural conventionalization, which is cross-linguistically parallel, with languages differing merely in degree.
Keywords: late-stage grammaticalization; language variation; cross-linguistic comparisons; subjunctive; conventionalization